An evaluation instrument for e-learning ecosystem - Chang, Vanessa (Institute of Electrical and Electronics Engineers (IEEE), 2008)
E-learning is now an acceptable medium of teaching and learning. The research development in this area has focused considerably in the technological and learning cognitive aspects such as assessing learning styles for individualized learning. These past work are vital to ensure continuous improving in e-learning systems. Given the long-standing research and development in e-learning, it is also necessary now to closely examine and evaluate the appropriateness of e-learning as a learning environment. In order to design a more effective learning environment, educators must now equip themselves with proper evaluation instrument. This paper will discuss the up-take of e-learning systems and e-learning ecosystems. A sustainable framework for e-learning ecosystems will be discussed. An instrument consisting of 4 elements or scales of Access, Interaction, Response and Results to evaluate e-learning systems is also discussed. This paper concludes with discussion regarding further work in this area.